2017
DOI: 10.1525/elementa.248
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to agroecological management through mediated markets in Santa Catarina, Brazil

Abstract: Agroecology, as a social movement and scientific discipline, applies ecological principles to the design and management of agricultural systems to improve environmental outcomes and livelihoods for farmers and rural communities. However, little research to date has assessed the policy mechanisms that could facilitate increased adoption of agroecological management practices. We investigated if and how public food procurement programs that provide financial incentives for organic and agroecological production c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
(42 reference statements)
0
22
0
6
Order By: Relevance
“…For example, the effects of public procurement may also be affected by farm size. Previous research in our study area showed that farm size influences farmer decisions to participate in PNAE (Guerra et al 2017). Furthermore, as a result of PNAE's market preference for fruit and vegetable crops, diversification may occur in some farm fields (e.g., horticultural plots where vegetables and fruits are cultivated), while in other fields (e.g., corn, soybeans, and other crops not directly consumed by households) "businessas-usual" management practices involving low diversity and intensive input use may remain.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…For example, the effects of public procurement may also be affected by farm size. Previous research in our study area showed that farm size influences farmer decisions to participate in PNAE (Guerra et al 2017). Furthermore, as a result of PNAE's market preference for fruit and vegetable crops, diversification may occur in some farm fields (e.g., horticultural plots where vegetables and fruits are cultivated), while in other fields (e.g., corn, soybeans, and other crops not directly consumed by households) "businessas-usual" management practices involving low diversity and intensive input use may remain.…”
Section: Introductionmentioning
confidence: 79%
“…Farm diversification exists along a continuum, but often includes agroecological management practices such as increased crop rotation complexity, cover cropping (i.e., use of non-harvested crops), use of organic nutrient sources such as legumes or manure, and biological control (Iverson et al 2014). Particular functional groups of crops, such as legume cover crops and perennials, increase functional diversity with plant traits that supply and retain nutrients and increase soil organic carbon storage (Blesh 2017). At larger scales, farm diversification can also reduce agriculture's contribution to global change by reducing external input dependency and associated greenhouse gas emissions.…”
Section: Farm Diversification and Food System Resiliencementioning
confidence: 99%
See 3 more Smart Citations